Dekonstruksi Perjanjian Dalam Hukum Perkawinan Islam - Arif, Muhammad; Widya Sari (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2023)
AbstractThis paper aims to examine the essence of the contract in marriage, the taklik divorce as an agreement, polygamy agreements as mandated in the Marriage Law and property agreements in marriage. Normatively, everything is understood based on an agreement either by using the term contract or the agreement itself. This is a literature review (library research). The data analysis method used is content analysis. The results of this study indicate that contract law norms as mandated in Article 2 KHI, basically cannot be perceived as an agreement but are